Pluralizing humanism : religions and secularisms beyond power - Jakelic, Slavica (Routledge, 2025)
"Humanism is appealed to today whenever we want to tackle the conditions of dehumanization in the contemporary world. But for humanism to be viable in the twenty first century, this book argues, it needs to be pluralized. Employing theoretical, historical and sociological arguments, the book moves beyond the discourse of critique. It engages theories of religion and secularism, as well as postmodern, postcolonial, and decolonial critiques of Western humanist projects, to uncover the ideas and practices of religious and secular humanisms when they challenge dehumanization in the pursuit of conditions of flourishing for all. Through studies of the Solidarity movement in Poland and the anti-apartheid movement in South Africa, the book demonstrates the centrality of humanist traditions to the emergence of religious-secular solidarities that transformed the political landscapes of the world. By highlighting the instances in which humanisms functioned as checks on each other's absolutist claims, the book contends that humanisms supply a constructive path for addressing the challenges of our time-a time of radically divided societies and intolerant, even violent, forms of nationalism. A challenge to the critiques of humanism that seek to identify it solely as the legacy of the West, as anti-religious discourse, or relegate it to the domain of power constellations, Pluralizing Humanism highlights the rich plurality of humanist discourses and the need for their mutual engagements. It points to humanist ideals as constitutive of politics that can guide our human power because they are irreducible to it. As such, the book will appeal to social scientists, social theorists, religious studies scholars, and ethicists with interests in religion, secularism, social movements, and humanist thought and practice"-- Provided by publisher.
Keywords: Humanism -- 21st century.; Pluralism -- History -- 21st century.; Protest movements -- 21st century.; elektronické knihy; electronic books